Energy Audit and Optimization of Energy Consumption in the Electronics Manufacturing Industry based on ISO 50001:2018 - Harits Ulhaq Hadyan, Abudhiya; Gagarin Irianto, Chairul; Alam, Syah (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
The development of modern science and technology, especially in the field of industry. Currently, It will grow every year in line with the increasing demand for electricity. The increase will be directly proportional to the increasing needs and production targets in the Electronics Industry. PT XYZ is a manufacturing industry that produces electronic products will use quantitative methods based on the ISO 50001: 2018 framework in companies that consume fossil energy from PLN sources. Industries that have a land area of 25,552.76 m². In 2022 the total energy consumption of PT XYZ amounted to 8,133.08 MWh kWh with an average of 677.75 MWh per month and is expected to increase by 2% in 2023. This research will computer loads as the most widely used loads in the Electronics Manufacturing Industry. Therefore, this research will determine the value of Energy Consumption Intensity (IKE) and determine Energy Saving Opportunities (PHE) based on ISO 50001: 2018 to facilitate assessments, decisions, and quick actions of relevant parties in saving electrical energy in order to minimize waste of electrical energy in accordance with the principles of energy management. The savings generated by this application reach 77,839 kWh/m² per year and potential electricity cost savings of around Rp 170,780,234.63 per year